SYNTHESIS AND CHARACTERIZATION OF 2-OXAZOLINE TELECHELIC POLYMERS - Gudiel Honores, Hellyn (2024)
New functionalized telechelic polymers containing ethyl xanthate and vinyl groups at the end of the chain were synthesized. The synthesis was carried out by the cationic ring-opening polymerization of 2-ethyl-2-oxazoline (Etoxa) and 2-methoxycarbonylethyl-2-oxazoline (Esteroxa) initiated by 1,4-trans-dibromobutene in acetonitrile at 78°C and finished by potassium ethyl xanthate or 4-vinylbenzyl-piperazine. The telechelic polymers were structurally characterized by nuclear magnetic resonance (1H NMR and 13C NMR) and infrared spectrometry. It was determined by 1H NMR that the degrees of polymerization of the telechelic polymers with ethyl xanthate and vinyl groups varied between 24-29 and 22-23 units, respectively, and were in agreement with the theoretical values. Also, for both types of telechelics, the molar percentages of Etoxa and Esteroxa agreed with the initial molar ratios of these monomers. The degree of functionality of the ethyl xanthate end groups in the telechelic polymers with ethyl xanthate varied between 64 to 82% and was 69 and 98% for the telechelic polymers terminated with vinyl groups.